The Effect Brand Awareness, Brand Association, and Perceived Quality on Brand Loyalty Through Guest Satisfaction as Mediation Variable at Hotel Le Grande Bali - Gede Adi Sistha Winata; I Ketut Surya Diarta; Ni Putu Ratna Sari (JURNAL KEPARIWISATAAN, 2023)
Hotel Le Grande experienced decreasing number of repeater guests and implemented  price war strategy to achieve room sales targets. The adoption of  price war strategy and decreased repeater guest consequences of low brand loyalty scores. This research model influences brand awareness, brand associations and quality perceptions on brand loyalty. Mediation of guest satisfaction is included as an answer in the relationship between exogenous and endogenous latent variables which are not consistent from previous studies. This study uses quantitative approach to examine the relationship between variables. The analysis used was quantitative based on multivariate analysis using structural equation model.  The data collection technique used was questionnaires with non-probability sampling technique in accidental sampling with  total of 100 samples. The results of this study show  direct relationship between exogenous latent variables have  significant and positive effect on endogenous latent variables. Indirect relationship through guest satisfaction as mediating variable, is only able to be a partial mediation on the influence of brand associations and perceived quality positively on brand loyalty. The implications of this study, hotel management should start respond to the low promotional value of brand awareness, association and perceived quality by creating good advertising materials, targeted activities and evaluating employee performance.